Pemberdayaan Masyarakat Dalam Meningkatkan Pengetahuan Ibu Tentang Pemberian Imunisasi Pada Bayi Usia 0-12 Bulan di Kelurahan Mangga Kecamatan Medan Tuntungan - Emelia Apriani Tampubolon; Rizky Andriani Bakara (Journal of Community Development, 2021)
Immunization is the provision of immunity against a disease and will only provide immunity or resistance to that disease, so if you need to avoid various diseases, other immunizations are needed. Immunization is very effective in preventing infectious diseases, through immunization our bodies will not be susceptible to infectious diseases (Faisal, 2021). There are two types of immunization, namely active immunization and passive immunization. National immunization programs include BCG, Hepatitis B, DTP, Polio, Hib and measles.The subjects in the service activities are mothers who have babies aged 0-12 months in Mangga Village, Ladang Bambu District, as many as 12 people. In the initial stage, an approach was made to the residents to deliver counseling material using the lecture method, immunization implementation assisted by the village midwife and followed by a question and answer session. Community service activities with the title "Community Empowerment in Improving Mothers' Knowledge about Immunization for Infants 0-12 Months of Age in Mangga Village, Medan Tuntungan District in 2022" were carried out on Friday, February 11, 2022 at 09.00 WIB until completion. When the activity began, residents came to register, then heard counseling material about increasing maternal knowledge about immunization in infants aged 0-12 months, weighing the baby's weight and TB, and carrying out immunizations assisted by village midwives. It is hoped that health workers will conduct health counseling to mothers who have babies aged 0-12 months, and mothers know the benefits of immunization which can reduce the incidence of disease, disability, and loss of life of a baby caused by infectious diseases.